Hierarchical porous−enhanced peroxymonosulfate activation via 3D ordered macro−microporous Fe−NC: Role of high−valent iron−oxo species and electron−transfer mechanism. (10th January 2023) - Tan, Ling; Xia, Yun; Wang, Shuyun; Fang, Xin; Yu, Yalin; Jiang, Fang; Chen, Huan
Abstract: Developing improved eco−friendly catalysts possessing high activity and simultaneously exhibiting adequate stability remains a bottleneck to date. By the means of introducing Fe along with constructing architecture, the novel 3D ordered macro–microporous Fe–NC catalyst (3DOM Fe–NC) was designed, which make the improvement on both activity and durability of carbonaceous catalysts become a reality. The introduction of Fe induces transformation of the active centers from carbonaceous framework to the formed FeNx sites, as well as alters PMS activation pathways, resulting in high−performance nonradical oxidation processes controlled by electron−transfer mechanism and high−valent iron−oxo species. Remarkably, owing to the alteration of active center, pollution adsorption on the carbonaceous frameworks is avoided that allows the 3DOM Fe−NC to prolong durability. Moreover, benefiting from the unique hierarchical architecture, the 3DOM Fe−NC/PMS system achieves superior activity and adaptability to the pollutants with different sizes. This work hopes to provide a new design concept for high−performance catalysts toward sustainable environmental remediation. Graphical abstract: Image 1 Highlights: The 3D ordered macro-microporous Fe-NC catalyst was successfully synthesized. The introduction of FeNx sites act as active centers to guide nonradical process. The enhanced stability of 3DOM Fe-NC stems from the alteration of active center. The designed hierarchical pores elevate the activity and flexibility of catalyst.